From the state theory of money to modern money theory: An alternative to economic orthodoxy - L. Randall Wray (Levy Economics Institute of Bard College, 2014)
This paper explores the intellectual history of the state, or chartalist, approach to money, from the early developers (Georg Friedrich Knapp and A. Mitchell Innes) through Joseph Schumpeter, John Maynard Keynes, and Abba Lerner, and on to modern exponents Hyman Minsky, Charles Goodhart, and Geoffrey Ingham. This literature became the foundation for Modern Money Theory (MMT). In the MMT approach, the state (or any other authority able to impose an obligation) imposes a liability in the form of a generalized, social, legal unit of account - a money - used for measuring the obligation. This approach does not require the preexistence of markets; indeed, it almost certainly predates them. Once the authorities can levy such obligations, they can name what fulfills any obligation by denominating those things that can be delivered; in other words, by pricing them. MMT thus links obligatory payments like taxes to the money of account as well as the currency. This leads to a revised view of money and sovereign finance. The paper concludes with an analysis of the policy options available to a modern government that issues its own currency.
Keywords: B1; B3; B15; B22; B25; B52; E40; E50; E62; H5; H60; N1; 330; Modern Money Theory; Chartalism; State Money; Knapp; Innes; Schumpeter; Keynes; Minsky; Goodhart; Ingham; Sovereign Currency